Hyperthermic Intraoperative Thoracoabdominal Chemotherapy. (10th May 2012) - Sugarbaker, Paul H.; Chang, David; Stuart, O. Anthony
Abstract : Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is a treatment option for selected patients with pseudomyxoma peritonei (PMP) and diffuse malignant peritoneal mesothelioma (DMPM). Tumor infiltration of the hemidiaphragm requiring partial resection occurs as a result of large volume and/or invasive disease at this anatomic site. Transmission of disease from abdomen to chest is a great danger in this group of patients. From a prospective database, patients who had diaphragm resection and then hyperthermic thoracoabdominal chemotherapy (HITAC) as a component of a cytoreductive surgical procedure were identified. Data from control patients receiving HIPEC or hyperthermic intrathoracic chemotherapy (HITOC) were analyzed for comparison. The morbidity, mortality, survival, and recurrence rate within the thoracic space were presented. Thirty patients had partial resection of a hemidiaphragm as part of a cytoreductive surgical procedure that utilized HITAC. The pharmacologic benefit of intracavitary chemotherapy administration was documented with an area under the curve ratio of intracavitary concentration times time to plasma concentration times time of 27 ± 10 for mitomycin C and 75 ± 26 for doxorubicin. Comparing percent chemotherapy absorbed for a ninety-minute treatment showed the largest for HIPEC, then for HITAC, and lowest for HITOC. The incidence of grade 3 and 4 adverse events was 43%. There was no mortality. Adjustments in the chemotherapy dose are not necessary with HITAC. The morbidity was high, the survival was acceptable, and intrathoracic recurrence was low.